SOME OF THE ISSUES OF LEGAL REGULATION OF RENT AGREEMENTSUNDER THE LAWS OF THE REPUBLIC OF KAZAKHSTAN - Indira Karzhaubaevna Елеусизова; Darkhan Meyrambekovich Шамшекбаев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article discusses some of the issues of legal regulation of rent agreementsunder the laws of the Republic of Kazakhstan and makes appropriate recommendations to improve the rules of civil law in this area.